(3cJGH aj GdaQhSjIs - (3fLe GdOjf eMeO Hf YjSi Hf ESeGYjd GdMfaj GdCMOHs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf agPG cJGH Ldjd GdbOQ cKjQ GdfaY ai eYQaI GdHfhO hYde GdaQhSjI s
(3BNQgG (B:s
(3hQei WGb eYdb ai Gdghi ecJhai HQei JHWjd hgPG BNQ GdHfhO s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(4 / 32(3b(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs